The Influence of Role Stress on Nurse Performance at Islam Faisal Hospital Makassar City - Achiruddin, Muh; Brasit, Nurdin; Wahda (Economics and Business Journal (ECBIS), 2023)
This study aims to determine whether role stress has an influence on the performance of nurses at the Faisal Islamic Hospital in Makassar City. The population in this study was 23 people, so a saturated sample was used to take the population as the sample. Data collection used by using observation and questionnaire methods. The data analysis technique used is simple linear regression analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that the role stress variable (X) has a negative and significant effect on the performance of nurses (Y) at Faisal Islamic Hospital Makassar City. Based on the results of the regression test, it was found that role stress (B = -0.586 and Sig. 0.000) had a negative and significant effect on nurse performance.